Penerapan Peran UMKM dalam Membangun Ekonomi Syariah di Kota Medan - Ariqah Luthfiyah; Atikah Humaidah; Dewi Fazira; Intan Alisa (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The development of Micro, Small and Medium Enterprises (MSMEs) is very important in supporting economic growth in the city of Medan. In the context of sharia economics, MSMEs act as the backbone of the economy, creating jobs, diversifying products, and empowering communities. However, they are faced with challenges such as limited access to capital, education, and regulations. This research analyzes the role of MSMEs from a sharia perspective, identifies challenges, and provides policy recommendations. The results show that MSMEs play an important role in overcoming poverty, creating diverse local products, and supporting an inclusive economy. Therefore, solutions are needed to financial, educational, marketing and regulatory challenges. Support from the government, financial institutions and universities together with sharia economic development can optimize the contribution of MSMEs in supporting sustainable economic growth in Medan City. In this way, MSMEs can become a driving force for economic growth which will have a positive impact on the people of Medan City.